Assessment of vulnerability status of public school children and existing school health programmes in Osun State, Nigeria - Adekemi E. Olowokere; Funmilayo A. Okanlawon (Elsevier, 2016)
This study was designed to assess the vulnerability status of school children, the public health response to their care and support while at the same time offers strategic suggestions for improved school health programmes. The research followed a descriptive mixed method cross-sectional design. The VC were recruited through a multistage sampling technique from two local government areas of Osun State, Nigeria. Data on vulnerability of school children were collected using vulnerability index (VI) while key informant interview gave the public health nurses the opportunity to share their experiences on public health services for school children. The data from the key informant interview were analysed by summarising key findings in theme while data collected from VC were analysed through descriptive and inferential statistics at 0.05 level of significance using SPSS version 16. A total number of 2484 school children were assessed. The mean age was 13 + 1.6 years. The result shows that 5.7% (n = 142) were not vulnerable, 68.0% (n = 1681) were vulnerable, 22.7% (n = 563) were more vulnerable while 3.6% (n = 90) were mostly vulnerable. The result established that a lot of children in public schools were vulnerable and there was shortage of public health manpower and services in place to meet their needs. The study revealed the needs of VC across the vulnerability indices. There is need for a viable school health programme for early identification of school children for prompt care and support.